SKRINING FITOKIMIA DAN UJI STABILITAS SEDIAAN SIRUP KAYU KUNING (Arcangelisia flava) UNTUK MEMELIHARA KESEHATAN - Ratnasari, Dewi; Handayani, Reti Puji (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2018)
Background: There are many studies explore the effectiveness and efficacy of yellow root, but while for phytochemical screening with decoction method and making of product has still little bit. Empirical yellow root is usually drunk in fresh condition, immediately after boiled, but cause of the bitter taste it needs to be covered by sweet taste and made product that can be last long. Options of honey for this research is intended to increase the taste of product that can be consumed in maintain health. Objective: This research is aimed to determine secondary metabolite content by decoction method, to make yellow root product and know the stability of yellow root product. Method: The yellow root research design used in this study is decoction method, tested the content of secondary metabolite, then added honey and tested organoleptis for 14 days. Conclusion: The results of phytochemical screening using decoction method showed that the yellow root extract contained alkaloids and saponins, and the stability test results showed more durable yellow wood extract plus honey.